The Role of Composition, Invasives, and Maintenance Emissions on Urban Forest Carbon Stocks (2015)
There are few field-based, empirical studies quantifying the effect of invasive trees and palms and maintenance-related carbon emissions on changes in urban forest carbon stocks. We estimated carbon (C) stock changes and tree maintenance-related C emissions in a subtropical urban forest by re-measuring a subsample of residential permanent plots during 2009 and 2011, using regional allometric biomass equations, and surveying residential homeowners near Orlando, FL, USA. The effect of native, non-native, invasive tree species and palms on C stocks and sequestration was also quantified. Findings show 17.8 tC/ha in stocks and 1.2 tC/ha/year of net sequestration. The most important species both by frequency of C stocks and sequestration were Quercus laurifolia Michx. and Quercus virginiana Mill., accounting for 20 % of all the trees measured; 60 % of carbon stocks and over 75 % of net C sequestration. Palms contributed to less than 1 % of the total C stocks. Natives comprised two-thirds of the tree population and sequestered 90 % of all C, while invasive trees and palms accounted for 5 % of net C sequestration. Overall, invasive and exotic trees had a limited contribution to total C stocks and sequestration. Annual tree-related maintenance C emissions were 0.1 % of total gross C sequestration. Plot-level tree, palm, and litter cover were correlated to C stocks and net sequestration. Findings can be used to complement existing urban forest C offset accounting and monitoring protocols and to better understand the role of invasive woody plants on urban ecosystem service provision.